ON ASPECT IN EVENTIVE AND AGENTIVE NOMINALIZATIONS IN SLOVENIAN - Tatjana Marvin (Philological Studies, 2019)
The paper deals with Slovenian deverbal nominalizations that denote events (gerunds in -je) and agents of events (agentive nominalizations in -ec), where special attention is paid to aspectual restrictions on the base. The paper tries to highlight the state of the aspect-related derivational rules in the contemporary Slovene language by analyzing data from the Slovene Literary Language Dictionary (Slovar slovenskega knjižnega jezika) and the corpus Gigafida.